2010
DOI: 10.1007/s00520-010-1045-0
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of anaemia and limited use of therapy in cancer patients: a Belgian survey (Anaemia Day 2008)

Abstract: Objectives The aim of this study is to provide relevant and accurate information on prevalence and treatment patterns of anaemia in Belgian cancer patients. Methods The Anaemia Day 2008 survey was a single visit, multi-centre, non-interventional study in adult cancer patients under systemic therapy (chemotherapy, hormonal, immunological and/or targeted therapy) and/or radiotherapy. Efforts were made to enrol the maximum number of patients seen in each centre that day. Patients signed an informed consent and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
14
4
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 15 publications
(18 reference statements)
7
14
4
4
Order By: Relevance
“…However, when only the patients receiving chemotherapy at enrollment were considered in the ECAS, 50% of them were found to be anemic (hemoglobin <12 g/dL)1 – a figure higher than observed here (39% were anemic based on hemoglobin levels ≤11 g/dL). Similarly, the prevalence of anemia, defined as hemoglobin levels <12 g/dL, was higher in the Belgian survey than in the present study (56% versus 39%) 14. However, the Belgian survey included patients with myelodysplasia, which was an exclusion criterion in the present study, and so increased reporting of anemia is to be expected in the former.…”
Section: Discussioncontrasting
confidence: 59%
“…However, when only the patients receiving chemotherapy at enrollment were considered in the ECAS, 50% of them were found to be anemic (hemoglobin <12 g/dL)1 – a figure higher than observed here (39% were anemic based on hemoglobin levels ≤11 g/dL). Similarly, the prevalence of anemia, defined as hemoglobin levels <12 g/dL, was higher in the Belgian survey than in the present study (56% versus 39%) 14. However, the Belgian survey included patients with myelodysplasia, which was an exclusion criterion in the present study, and so increased reporting of anemia is to be expected in the former.…”
Section: Discussioncontrasting
confidence: 59%
“…This finding was in agreement with the studies done by other researchers [3,12]. The sex distribution above was found to be in contrast to many other studies which showed that male cancer patients generally were in higher proportion than female cancer patients [13][14][15][16][17]. This may be due to the differences in population studied or treatment options at the facility.…”
Section: Discussionsupporting
confidence: 92%
“…Out of 201 patients studied, 54% (108) had WHO performance status of 0 while 46% (93) had WHO performance status of 1. The correlation between patients's WHO performance status Hb levels was elucidated by Natacha et al in their study of 1,403 cancer patients [13]. In their study, there were more patients at enrolment with poor performance status at lower Hb level than at higher Hb levels.…”
Section: Discussionmentioning
confidence: 95%
“…11 The prevalence of all grades of anemia has been estimated to be as high as 65% and more specifically as high as 20% for grade 3 and 4 anemia (hemoglobin level, G8 g/dL). 1,12,13 The importance of anemia in patients with cancer stems from its association with a poor prognosis and a 65% greater risk in overall mortality.…”
Section: Discussionmentioning
confidence: 99%